Kohabitasi dalam Bingkai Hukum Positif Indonesia: Kajian Normatif Atas Larangan, Kriminalisasi, dan Problematika Penegakan Hukumnya - Cindy Wi; Elly Sudarti; Taufik Yahya (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2026)
Cohabitation—defined as the practice of two unmarried individuals living together in an intimate relationship—presents a growing normative challenge in Indonesian society, which maintains a theistic constitutional foundation while navigating rapid social change. This article examines cohabitation through three juridical lenses: first, the regulatory architecture through which Indonesian law prohibits cohabitation; second, the criminalization framework established under Law Number 1 of 2023 on the National Criminal Code; and third, the practical and theoretical problems that emerge in law enforcement. Employing a normative legal research methodology that integrates statutory, conceptual, and comparative approaches, this study finds that prohibitions against cohabitation are embedded across multiple regulatory layers—spanning marriage law, customary law, codified Islamic law, and regional legislation. The National Criminal Code, through Articles 412 and 413, introduces for the first time an explicit criminalization of cohabitation within Indonesia's post-independence penal codification. Nevertheless, the complaint-based offense structure, evidentiary challenges, and persistent tension between formal norms and social realities produce a substantial implementation gap. The study concludes that legal effectiveness in addressing cohabitation requires coordinated action across criminal enforcement, family institution strengthening, and sustained legal literacy programs.